Unlocking the potential of game-based learning for soft skills development: A comprehensive review - Tan, Bee Sian; Chong, Kim Soon (Journal of ICT in Education, 2023)
Soft skills are critical for undergraduate students to succeed in the workplace, but there exists a gap between the skills possessed by undergraduate students and those required by the industry. This review explores the use of game-based learning (GBL) for developing soft skills among undergraduate students. The review aims to answer four research questions that cover essential aspects of GBL, such as its theoretical foundation, skill development, game design elements, and assessment methods. Following the Preferred Reporting for Systematic Reviews and Meta-Analysis (PRISMA) guidelines, we selected 24 journal articles with empirical results from Scopus databases spanning 2017 to 2023, applying inclusion and exclusion criteria to finalize 18 articles for review. The review identified potential challenges in using GBL for soft skills development, such as the exploration of least developed soft skills, effectiveness of theoretical foundation adoption, game design elements development, and validation of assessment methods. This study aims to provide recommendations for game designers and educators to enhance GBL for soft skills development. The study proposes integrating established learning theories with emerging technologies and social media to provide a personalised learning experience, exploring generative AI in soft skills games, designing open-ended or sandbox game environments to develop innovation skills, incorporating in-game assessment features to assess self-management skills, aligning game rewards with learning objectives, encouraging peer-to-peer assessment, and collaborating with psychometricians to align captured data with the intended soft skills assessment. The study also highlights limitations and suggests future studies to address them, such as adopting emerging technologies to address limitations. Overall, the study contributes to the understanding of GBL for soft skills development and provides valuable insights and recommendations for future research and practice in this domain.